Der Briefwechsel mit den Jesuiten in China (1689-1714) - Leibniz, Gottfried Wilhelm 1646-1716; Bouvet, Joachim 1656-1730; Widmaier, Rita; Babin, Malte-Ludolf (Hamburg Meiner, 2006)
In the last decades of the seventeenth century, debates about China took place among the intellectual elite, particularly in Germany and France. This was in response to the publications of the Jesuits' mission in China. Of all his contemporaries, Leibniz wrote the most on the subject. In 1710 he received a letter from Joachim Bouvet, the leading figure in China among the Jesuits of the movement of figurism, a method of interpreting the Thirteen Classics, a collection of Chinese writings that collectively form the canon of Confucianism. In the letter, Bouvet stated, he had found Leibniz's binary number system in the 64 hexagrams of the Book of Changes.The 64 hexagrams of this work were arranged in a mathematically exact sequence, each line containing one long or two short strokes. After this, Leibniz began an extensive correspondence with Jesuits in China. He supported them in the Contest of Rites concerning the question of whether or not Chinese rites could be accommodated in the practice of the Christian faith there. In 1699 his most important work on the subject was published: the 'Novissima Sinica'. He saw similarities between Chinese philosophy and his own views and advocated a further exchange of knowledge between European and Chinese philosophers that would lead to a better understanding of Creation. He proposed that the Chinese natural religion be preached in Europe. Leibniz considered China superior in both practical philosophy and moral instruction.
Keywords: Jesuits; 17th Century (1601-1700); Correspondence; Philosophy; Germany; China